Off to the park: a geospatial investigation of adapted ride-on car usage. - Hoffman, Mia E.; Steele, Katherine M.; Froehlich, Jon E.; Winfree, Kyle N.; Feldner, Heather A. (Disability & Rehabilitation: Assistive Technology, 2024)
Adapted ride-on cars (ROC) are an affordable, power mobility training tool for young children with disabilities. Previous qualitative research has identified environmental factors, such as weather and adequate drive space, as barriers to families' adoption of their ROC. However, we do not currently know the relationship between the built environment and ROC usage. In our current study, we quantified the driving patterns of 14 children (2.5 ± 1.45 years old, 8 male: 6 female) using ROCs outside and inside of their homes over the course of a year using a custom datalogger and geospatial data. To measure environmental accessibility, we used the AccessScore from Project Sidewalk, an open-source accessibility mapping initiative, and the Walk Score, a measure of neighborhood pedestrian-friendliness. The number of play sessions with the ROC ranged from 1 to 76; 4 participants used it less than 10 times and 4 participants used it more than 50 times. Our findings indicate that more play sessions took place indoors, within the participants' homes. However, when the ROC was used outside the home, children engaged in longer play sessions, actively drove for a larger portion of the session, and covered greater distances. Most children tended to drive their ROCs in close proximity to their homes, with an average maximum distance from home of 181 meters. Most notably, we found that children drove more in pedestrian-friendly neighborhoods and when in proximity to accessible paths. The accessibility of the built environment is paramount when providing any form of mobility device to a child. Providing an accessible place for a child to move, play, and explore is critical in helping a child and family adopt the mobility device into their daily life. Ride-on cars provided a novel means for young children with disabilities to explore their home and community environments. Children drove their adapted ride-on cars for longer periods of time outside than inside, and in close proximity to their homes. The identification of an accessible route increased driving frequency and drive session duration. Recommending accessible routes and play locations where families can use their adapted ride-on car may be an important aspect of increasing mobility technology use. Because there were a higher number of play sessions inside, it is important to consider indoor accessibility when designing and implementing mobility technology for young children.